Alkaline-washed phosphogypsum-based cemented paste backfill prepared using steel slag and blast furnace slag: Mechanical properties, fluoride immobilization, and hydration mechanism - Qiusong Chen; Lingzhi Gao; Aixiang Wu; Yan Feng; Yunbo Tao; Daolin Wang (Case Studies in Construction Materials)
Phosphogypsum (PG)-based cemented paste backfill (PCPB) is an effective way to deal with the problem of PG storage, but the low strength, high cost, and serious fluoride pollution of PCPB limit the popularization of this technology. Alkaline washing has been proven to be an effective means to decrease fluoride from PG. Steel slag (SS) and ground granulated blast furnace slag (GGBFS) are common materials possessing pozzolanic activity. SS and GGBFS can be employed as cement substitutes under alkaline conditions. This paper proposes the combined heuristic effect of NaOH pretreatment, SS, and GGBFS to improve the strength of alkaline-washed PCPB (APCPB) and the ability of fluoride immobilization. The study results show that alkali washing stimulates the secondary hydration activity of solid waste materials and promotes the formation of hydration products such as AFt and C-S-H so that the UCS value of APCPB increases greatly in the later stages of hydration increases by 309.8 % (7.06 MPa), and the leaching concentration of fluoride decreases by 21.5 % (0.85 mg/L). Through microscopic characterization experiments on the APCPB, it was discovered that in the alkaline hydration system, the transformation of C-S-H and AFt into C-A-S-H, F-C-S-H, and F-AFm, coupled with the physical encapsulation of hydration products, are the main factors immobilizing fluoride. This work provides a much-needed supplement to the in-situ cement-free repair technology of PG in mines to develop more lower-carbon and environmentally friendly mixture formulations.